Polyamines in the Synthesis of Bacteriophage Deoxyribonucleic Acid II. Requirement for Polyamines in T4 Infection of a Polyamine Auxotroph - Dion, Arnold S. (1972)
Polyamine depletion produced by exogenous arginine in Escherichia coliK-12 cultures defective in agmatine ureohydrolase activity resulted in a marked inhibition of the rates of growth and nucleic acid synthesis. Addition of putrescine or spermidine to such depleted cultures restored the control rate of growth and nucleic acid accumulation. The omission of lysine resulted in a further decrease in the rates of growth and nucleic acid synthesis in polyamine-depleted cells. The addition of exogenous cadaverine increased the rates of growth and ribonucleic acid synthesis to those observed in lysine-supplemented cultures, suggesting that lysine or a derivative of lysine serves a function similar to cadaverine. Addition of lysine to polyamine-depleted cultures at neutral pH results in the synthesis of cadaverine and a new spermidine analogue, both containing lysine carbon. This new metabolite has been isolated and identified as N-3-aminopropyl-1, 5-diaminopentane. T4D infection of the polyamine-depleted mutant resulted in a very low rate of DNA synthesis and phage maturation. The addition of putrescine or spermidine 15 min before infection restored phage DNA synthesis and phage maturation to control rates, i.e., rates observed in infected cells grown in the absence of arginine.